Relevansi Strategi Pembelajaran Ekspositori untuk para Santri PonPes I’anah Futuhiyah di Pemalang - Fadli, Alfan Aqil; Subhi, Muhamad Rifai; Mustakim, Zaenal (The Magister of Islamic Education IAIN Pontianak, 2025)
Learning in Pondok Pesantren I'anah Futuhiyah Pemalang is still dominated by the traditional lecture method, this study aims to examine the relevance of expository learning strategies for students. Problems related to learning in PonPes I'anah Futuhiyah still exist, the advantages and disadvantages of expository learning strategies for relevance in the era of modernization. The method used is descriptive qualitative research method by means of researchers observing at PonPes I'anah Futuhiyah Pemalang and interviewing directly to informants as the main source and using archival documentation data to strengthen the results of the study. The results showed that the expository learning strategy is relevant to the needs of students in improving understanding and motivation to learn. This strategy allows teachers to deliver subject matter in a systematic and structured manner. The advantage of this strategy is that the teacher is easier to control the order and amount of learning material. However, this strategy also has weaknesses, such as the lack of interaction between teachers and students, as well as the potential for students to become passive in the learning process. This strategy can help improve students' speaking skills and communication abilities. This strategy is also in accordance with the vision and mission of the boarding school in developing quality students. Data analysis shows that the expository learning strategy helps students understand the material